Characterization of Biobriquette from Carbonized Durian Peel Using Coconut Shell as the Binder - Soeherman, Giffary Pramafisi; Putri, Pridata Gina; Joen, Deary Amethy Zahrotinufus; Indrawan, Iyan; Pratiwi, Nurma (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This research aimed to study the characteristics of carbonized durian peel biobriquette using tar as a binder. A 1:10 ratio of binder and carbonized durian peel was used. The 25, 50, and 75% (coded as P1, P2, and P3, respectively) tar were used as a binder alongside tapioca flour to produce a binder with different tar concentrations. The briquette characteristics determined moisture content, ash content, calorific value, density, and water-absorbing capacity. Moisture content ranged from 9.32% to 9,41% for treatments P1 to P3, while the ash content ranged from 12,29% to 13,09%, showing no significant difference among the treatments. Massive difference was observed in calorific value, as P1 gives 5106/35 cal g-1 calorific value while P2 and P3 give 9267.56 and 9694.53 cal g-1, respectively. The density observed was relatively low, ranging from 0.5029 g cm-3 to 0,5685 g cm-2. As for water-absorbing capacity, P3 absorbed the least amount of water, 29.43%. From this research, we can conclude that coconut shell tar has the potential to be utilized as a binder in forming biobriquette from carbonized durian peel.